The experience of fatigue in people with inflammatory bowel disease: an exploratory study. (6th December 2012) - Czuber‐Dochan, Wladyslawa; Dibley, Lesley B.; Terry, Helen; Ream, Emma; Norton, Christine
Abstract Aims To explore fatigue, the impact it has on daily life and the strategies used to ameliorate the symptom, as described by people with inflammatory bowel disease. Background Fatigue is the most troublesome symptom during remission of inflammatory bowel disease. Fatigue affects people's daily functioning, impacting on quality of life. There is limited understanding of the nature of and the ways fatigue in inflammatory bowel disease is experienced and managed in everyday adult life. Design An epistemological interpretive approach to understand participants' self‐reported experiences of disease‐related fatigue. Methods A convenience sample of 46 participants was recruited from the Crohn's and Colitis UK member database. Five focus group interviews (November 2008–February 2009) were conducted, audio‐recorded, transcribed, and analysed using an inductive thematic framework. Findings Five themes were identified: the experience of fatigue, causes of fatigue, managing fatigue, consequences of fatigue, and seeking support. Fatigue had a debilitating effect on the social and emotional well‐being of participants and limited their employment opportunities. People used a range of strategies to cope and reported that fatigue‐related issues seemed to be poorly understood by clinicians and were not addressed in medical consultations. Conclusion Fatigue was an inextricable part of daily life for some people with inflammatory bowel disease. Specialist nurses and medical colleagues need to address the personal, social, and economic consequences of fatigue, whilst further nursing research would improve understanding of the impact of fatigue and help develop appropriate intervention strategies for people with inflammatory bowel disease.